Volunteer and clinical studies with carfecillin: a new orally administered ester of carbenicillin. Issue 5965 (3rd May 1975) - Wilkinson, P J; Reeves, D S; Wise, R; Allen, J T
Abstract : Blood and urine levels of carbenicillin were measured in 10 healthy volunteers and four patients with renal failure after single and multiple oral dose of carfecillin. Urinary levels after 1000-mg doses in healthy subjects were considered sufficient for treatment of Pseudomonas aeruginosa urinary infections, but the serum levels were too low for chemotherapy of systemic infections with this organism even in severe renal failure. Urinary infections were treated in 35 inpatients with a seven-day course of carfecillin. The infection was eradicated in 21 cases (60%). In 12 cases the pathogen was Ps. aeruginosa, which was eradicated from eight patients (67%). Many patients had severe urinary tract disease. Side effects were virtually absent.